WHISTLEBLOWING SYSTEM DAN PERAN AUDIT INTERNAL DALAM MENCEGAH FRAUD - Ummu Fitriani Basri (Universitas Islam Negeri Alauddin Makassar, 2021)
Companies based on the principles of Good Corporate Governance (GCG) can achieve their vision, mission, and goals for the better. One form of GCG implementation is the whistleblowing system. In addition to better corporate governance, the Whistleblowing system appears due to the increasing number of cases of fraud (fraud), financial irregularities, and part of an internal control. To reduce these fraud cases, a whistleblowing system was formed which is expected to be an effective tool in minimizing fraud in companies and governments. In this study, a qualitative research methodology was used. This type of research is library research. The approach used in this research is a philosophical and pedagogical approach. The results of the study indicate that within the scope of the ministry of finance, the Whistleblowing System has been regulated in the Peraturan Menteri Keuangan Nomor 103/Pmk.09/2010 concerning Procedures for Management and Follow-Up of Reporting Violations (Whistleblowing) in the Ministry of Finance.